Control Interno A Inventarios Y Su Impacto En Los Estados Financieros De La Empresa Cárnicos Pucayacu, Cantón La Maná. Año 2023 - Daza Salazar, Juan Carlos (2025)
The impact of internal inventory control on the Financial Statements of the company Cárnicos Pucayacu for the period 2023 was evaluated. This evaluation was carried out in the Canton La Maná. In order to fulfill the specific objectives, the procedures and tools of internal control in the inventory area were analyzed through an observation guide. Likewise, the degree of compliance with Section 13 of IFRS for SMEs was evaluated and finally, the benefits that the company obtains by complying with adequate inventory management were determined. The structuring of the theoretical framework was carried out through scientific articles, books and regulations applicable to the research topic. The type of research was mixed (qualitative-quantitative), the methodology that was applied to reach the results of this project was the analytical, inductive and deductive method, among the techniques that were used were an internal control questionnaire to the personnel in charge of storage and an interview with the general accountant. Based on the results obtained, recommendations were established that are aligned with the improvement of internal control in inventories.